2022
DOI: 10.3390/su14116429
|View full text |Cite
|
Sign up to set email alerts
|

Innovativeness as the Key to MSMEs’ Performances

Abstract: Research on Micro Small Medium Enterprises (MSME) has always been an exciting area of study because of its crucial role; however, it turns out that MSMEs have many problems. The problems, such as human resources and their abilities, are rarely discussed. MSMEs tend to be formed because of a compulsion to do so, whereas companies are created by opportunities; therefore, it is essential to include entrepreneur orientation and dynamic capability elements in making MSME performance models. This study used SEM anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
10

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 82 publications
0
13
0
10
Order By: Relevance
“…As an important part of implementing an innovation strategy, innovation processes and innovation systems are stated to be able to increase sustainable competitive advantage in MSMEs (Aminullah et al, 2022;Candraningrat et al, 2021;Gao et al, 2023). Research on innovation strategy shows that processes and systems have a significant impact and emphasizes the need for special efforts to implement innovation at a strategic level, especially with active efforts to update products and services to respond to diverse market needs (Kilay et al, 2022;Octasylva et al, 2022;Suharyati & Utami, 2022). Understanding the importance of business predictions among Yogyakarta MSMEs is crucial by using forecasting techniques.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…As an important part of implementing an innovation strategy, innovation processes and innovation systems are stated to be able to increase sustainable competitive advantage in MSMEs (Aminullah et al, 2022;Candraningrat et al, 2021;Gao et al, 2023). Research on innovation strategy shows that processes and systems have a significant impact and emphasizes the need for special efforts to implement innovation at a strategic level, especially with active efforts to update products and services to respond to diverse market needs (Kilay et al, 2022;Octasylva et al, 2022;Suharyati & Utami, 2022). Understanding the importance of business predictions among Yogyakarta MSMEs is crucial by using forecasting techniques.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Furthermore, in manufacturing MSMEs, it has been discovered that innovation capability positively correlates with company performance (Vijayakumar & Chandrasekar, 2022). Additionally, elements including organizational culture, knowledge management, and entrepreneurial orientation can operate as moderators in the relationship between innovation and MSME success (Octasylva et al, 2022). It was also discovered that the traits held by MSME owners have an impact on innovation, which in turn has an impact on performance.…”
Section: Innovation and Msme Performancementioning
confidence: 99%
“…To excel in financial innovation and a strong intellectual and functional capacity to operate an organisation, the mechanism of sensing, intuition, feeling, and thought must be built by MSME owners and start-up entrepreneurs. This enables MSMEs to embrace financial uncertainties to achieve relevance, survival and sales growth (Gibcus, 2003;Octasylva et al, 2022). The foundation of the survival strategy is that to survive, SME firms need to constantly adapt to their competitive financial climate.…”
Section: Survival-based Theorymentioning
confidence: 99%
“…This theory, which was very popular during the late 19th and early 20th centuries, stressed the notion that only the best and fittest of MSME competitors would benefit by pursuing the concept of design, which eventually would lead to the development of a creative and innovative service or product. The survival-based view of the management emphasized the assumption that businesses that follow financial strategies that focus on running very productive activities would thrive in a competitive environment (Egwakhe, et al, 2020;Octasylva, et al, 2022). These scholars concluded that the most equipped and willing MSME owners and start-up entrepreneurs that adapt to the favourable financial and environmental business climate is the organisation that succeeds.…”
Section: Survival-based Theorymentioning
confidence: 99%